Lung transplantation for chronic obstructive pulmonary disease - Liou TG; Raman SM; Cahill BC (Transplant Research and Risk Management, 2013)
Theodore G Liou, Sanjeev M Raman, Barbara C CahillDivision of Respiratory, Critical Care and Occupational Pulmonary Medicine, Department of Medicine, School of Medicine, University of Utah, Salt Lake City, Utah, USAAbstract: Patients with end-stage chronic obstructive pulmonary disease (COPD) comprise the largest single lung disease group undergoing transplantation. Selection of appropriate candidates requires consideration of specific clinical characteristics, prognosis in the absence of transplantation, and likely outcome of transplantation. Increased availability of alternatives to transplantation for end-stage patients and the many efforts to increase the supply of donor organs have complicated decision making for selecting transplant candidates. Many years of technical and clinical refinements in lung transplantation methods have improved survival and quality of life outcomes. Further advances will probably come from improved selection methods for the procedure. Because no prospective trial has been performed, and because of confounding and informative censoring bias inherent in the transplant selection process in studies of the existing experience, the survival effect of lung transplant in COPD patients remains undefined. There is a lack of conclusive data on the impact of lung transplantation on quality of life. For some patients with end-stage COPD, lung transplantation remains the only option for further treatment with a hope of improved survival and quality of life. A prospective trial of lung transplantation is needed to provide better guidance concerning survival benefit, resource utilization, and quality of life effects for patients with COPD.Keywords: outcomes, emphysema, COPD, alpha-1-antitrypsin deficiency, survival, single lung transplant, bilateral sequential single lung transplant, lung volume reduction, referral, guidelines, health related quality of life